x → 0 lim ( cos x ) 1 / x 2 = ?
Give your answer to 1 decimal place.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: L'Hopital's Rule - Basic
L = x → 0 lim ( cos x ) x 2 1 = exp ( x → 0 lim x 2 cos x − 1 ) = exp ( x → 0 lim 2 x − sin x ) = exp ( x → 0 lim 2 − cos x ) = e − 2 1 = e 1 ≈ 0 . 6 0 7 A 1 ∞ case, use x → a lim ( g ( x ) f ( x ) ) h ( x ) = e lim x → a h ( x ) ( g ( x ) f ( x ) − 1 ) A 0/0 cases, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x Differentiate up and down again
You worked a lot, You should have done it in the third step only, Why u again differentiated?
Log in to reply
I know lim x → 0 x sin x = 1 . Just want to show that how we get it. Of course we can also get it from Maclaurin's series.
Problem Loading...
Note Loading...
Set Loading...
Express y ln ( y ) = lim x → 0 ( cos ( x ) ) 1 / x 2 = lim x → 0 x 2 1 ln ( cos ( x ) ) = lim x → 0 x 2 ln ( cos ( x ) ) Since as x → 0 , x 2 ln ( cos ( x ) ) → 0 0 . In this case, apply L'Hôpital's Rule to get lim x → 0 d x d [ x 2 ] d x d [ ln ( cos ( x ) ) ] = lim x → 0 2 x − cos ( x ) sin ( x ) = lim x → 0 − 2 x cos ( x ) sin ( x ) = − 2 1 lim x → 0 x cos ( x ) sin ( x ) Because x → 0 lim f ( x ) g ( x ) = x → 0 lim f ( x ) ⋅ x → 0 lim g ( x ) where f ( x ) = x sin ( x ) and g ( x ) = cos ( x ) 1 , we express the limit as − 2 1 ( x → 0 lim x sin ( x ) ) ( x → 0 lim cos ( x ) 1 ) Since x → 0 lim x sin ( x ) = 1 and x → 0 lim cos ( x ) 1 = 1 ln ( y ) ln ( y ) y = − 2 1 ( lim x → 0 x sin ( x ) ) ( lim x → 0 cos ( x ) 1 ) = − 2 1 ⋅ 1 ⋅ 1 = − 2 1 = e − 1 / 2 = e 1 Thus, e − 1 / 2 ≈ 0 . 6 0 6 .